Less Likely to Fail: Low Performance, Firm Size, and Factory Expansion in the Shipbuilding Industry - Audia, Pino G.; Greve, Henrich R. (Management Science, 2006)
The behavioral theory of the firm and prospect theory predict that performance below an aspiration level increases risk taking, but researchers also propose that performance below an aspiration level decreases risk taking. These conflicting predictions primarily hinge on whether decision makers perceive negative performance as a repairable gap or as a threat to firm survival. This study examines a boundary condition of these conflicting predictions. We argue that a firm’s resource endowment affects decision makers’ risk tolerance: Managers in firms with large stocks of resources are buffered from the threat of failure and conform to the prediction of greater risk taking in response to performance decreases; managers in firms with limited resources view low performance as a step closer to failure and decrease risk taking in response to performance decreases. Using data on the risky decision of factory expansion in shipbuilding firms and firm size as an indicator of the stock of tangible resources, we find that performance below the aspiration level reduces risk taking in small firms, but either does not affect risk taking or increases risk taking in large firms. These findings are largely consistent with our predictions and also suggest that large firms are more inert than small firms.